RELASI ISLAM DAN SAINS UNTUK MEMBANGUN MODERNITAS - Nurcholish Fairuzabady; Iffan Ahmad Gufro; Masykur (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the relationship between Islam and science by highlighting three main aspects: first, the relationship between Islam and science; second, the integration of Islam and science; and third, the contribution of Islam and science in building modernity. The problem of the relationship between science and religion, especially in the form of interaction and its methodological aspects, is the main focus of this study. The analysis was carried out by exploring the thoughts of several figures from various academic backgrounds. The philosophy of science is used as a conceptual framework for understanding and answering the three main problems studied. The results show that although science and religion are two different domains that provide knowledge and meaning to human existence, the interaction between the two is dynamic. Relationships that were previously marked by confrontation and conflict develop into relationships that affect each other in the process of modernity's development. The thinkers in this study use the scientific method as the main instrument in acquiring knowledge. Apart from the existing epistemological differences, there is a common ground between religion and science in their contribution to the development of human civilization holistically. This study uses a qualitative method with a phenomenological approach to understand the pattern of interaction between Islam and science and its impact on the development of civilization